KONTRIBUSI INSTAGRAM TERHADAP PERILAKU KONSUMTIF MAHASISWA IAIN KERINCI - Ahmad Khairul Nuzuli; Annisa Aulia Pratama; Alwan Daffa Rendra; Cahyu Annisa; Destria Amita; Datin Rahmawati; Force Atmayutes; Intan Fuji Lestari (GoAcademica Research dan Publishing, 2022)
Instagram is a social network, not infrequently this social media is considered a very effective means of conducting sales promotions, online shops on Instagram appear at prices that are quite competitive with other online shop prices, this can generate one's shopping interest. This study aims to see the contribution of Instagram to the consumptive behavior of IAIN Kerinci students. The research method used is descriptive qualitative method. The research results show that; the first, consumptive behavior of students is influenced by the many attractive advertisements and quality goods on Instagram. Second, attractive advertisements on Instagram make consumers tempted so that they shop frequently. Third, consumptive behavior can affect a person's lifestyle into hedonism which is caused by continuous and excessive shopping behavior without thinking about spending or budget and ignoring things that are actually their needs. With this, the researchers suggest changing the mindset from consumptive to productive, we must look at things based on their productivity, and realize that life is not just for pleasure.